The Evaluation of Driver Behaviors and Skills Relation with Consumption of Alcohol, Drug Abuse and Medicine in Professional Drivers - Aktaş, Alev; Döğer, Rukiye; Akgür, Serap Annette (The Bulletin of Legal Medicine, 2019)
Introduction: Driver behavior and skills are among the main factors that constitute the risk of accidents in traffic. Driving behavior under the influence of alcohol and drug abuse is an important traffic problem that causes deaths, pecuniary damage and injuries. The aim of the study was to investigate the frequency of alcohol, drug abuse and medicine use in professional drivers and to evaluate the relationship between these substances and driver behavior and skills. Methods: The study was performed with 90 professional drivers working in 4 different town of İzmir. questionnaire form, Fagerström Test for Nicotine Dependence (FTND), CAGE Alcohol Screening Test, Driver Behavior Scale (DBS) and Driving Skills Scale (DSS) were applied to drivers. The data were analyzed statistically with SPSS 18.0 (p <0.05 significance level). Results: Drivers were between the ages of 20-67 and the average age was 42,9 ± 12,7 years. 46,7% of them have been professional drivers for more than 20 years. The majority of drivers used cigarettes (57,8%) and alcohol (63,3%). The reported substances and drugs use percentage from drivers were 55,6% painkillers to increase their attention and/or alertness in traffic, 12,2% tranquilizers, 1,1% steroids, 20% cannabis, 3,3% amphetamine-type stimulants (ATS), 2,2 % synthetic cannabis at least once through their life-time. Significant differences were found between alcohol and cannabis use and errors, rule violations and the ability to safe driving. Conclusion: It will be useful to consider driving behavior well-rounded with psychological, psychiatric and forensic toxicological aspects. The results of our study showed that drug abuse...